2,2 `-(Disulfanediyl)dibenzoic acid-2,9-dimethylphenanthroline-tetrahydrofuran (1/2/1) - Arman, H.D.; Kaulgud, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The asymmetric unit of the title co-crystal solvate, C(14)H(10)O(4)S(2)center dot 2C(14)H(12)N(2)center dot C(4)H(8)O, comprises a 2,2'-(disulfanediyl) dibenzoic acid molecule, two molecules of 2,9-dimethylphenanthroline and a tetrahydrofuran (THF) solvent molecule. Each end of the twisted diacid [dihedral angle between the benzene rings = 74.33 (17)degrees] forms a strong O-H center dot center dot center dot N hydrogen bond with a 2,9-dimethylphenanthroline molecule, forming a trimeric aggregate. The crystal structure comprises layers of acid and THF molecules, and layers of 2,9-dimethylphenanthroline molecules that alternate along the a axis, the main connections between them being of the type C-H center dot center dot center dot O.